Rapid iPSC-derived neuromuscular junction model uncovers motor neuron dominance in amyotrophic lateral sclerosis cytopathy - Hsiao-Chien Ting; Yun-Ting Guo; Hong-Lin Su; Yu-Shuan Chen; Shinn-Zong Lin; Horng-Jyh Harn; Chia-Yu Chang (Cell Death Discovery)
Abstract The neuromuscular junction (NMJ) is essential for transmitting signals from motor neurons (MNs) to skeletal muscles (SKMs), and its dysfunction can lead to severe motor disorders. However, our understanding of the NMJ is limited by the absence of accurate human models. Although human induced pluripotent stem cell (iPSC)-derived models have advanced NMJ research, their application is constrained by challenges such as limited differentiation efficiency, lengthy generation times, and cryopreservation difficulties. To overcome these limitations, we developed a rapid human NMJ model using cryopreserved MNs and SKMs derived from iPSCs. Within 12 days of coculture, we successfully recreated NMJ-specific connectivity that closely mirrors in vivo synapse formation. Using this model, we investigated amyotrophic lateral sclerosis (ALS) and replicated ALS-specific NMJ cytopathies with SOD1 mutant and corrected isogenic iPSC lines. Quantitative analysis of 3D confocal microscopy images revealed a critical role of MNs in initiating ALS-related NMJ cytopathies, characterized by alterations in the volume, number, intensity, and distribution of acetylcholine receptors, ultimately leading to impaired muscle contractions. Our rapid and precise in vitro NMJ model offers significant potential for advancing research on NMJ physiology and pathology, as well as for developing treatments for NMJ-related diseases.